The influence of the teams games tournament type cooperative learning model on elementary school students' mathematics learning outcomes - Sai'in, Gita Puspita; Yusrizal, Yusrizal; Nazaruddin, Ilham (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to determine the effect of a team game tournament learning model on the mathematical performance of high school students using blocks and cubes as instructional tools. This experimental design consists of a pre- and post-test control group with twenty samples each. This study included a total of 60 students from Grade V SD IT Syifaurrahmah Patumbak, with 30 students from Grade VA and 30 students from Grade VB serving as samples. The homogeneity test is carried out in accordance with the research results after the normality test. The results of students' mathematics learning were influenced by the teaching model of teams games tournament, according to statistical data (p = 0.026 < 0.05). The results show that this model rejects the null hypothesis and supports the alternative hypothesis.